A new isoflavonc from Jacaranda obtusifolia H.B.K. ssp. rhombifolia (G.F.W. Meijer) gentry - Sorachai Khamsan (2018)
© 2011 University of Istanbul. All rights reserved. A new isoflavone (1), along wilh daidzein (2), and genistin (3) were isolated from the Jacaranda oblusifolia twig extract. Their structures were elucidated by NMR and MS spectroscopy. Compound 1 possessed significant anticancer activity against KB and NC1-H187 cell lines with the IC50values of 2.52 and 7.47 ng mL-1, compound 2 and 3 exhibited anticancer activity against KB and NC1-HI87 cell lines wilh the IC50values of 5.73, 8.14, 2.83 and 27.30 μg mL-1, respectively. Compound 2 also showed anticancer activity against MCF-7 cell line with an IC50value of 28.17 μg mL-1. The isolates showed non-cytotoxic against Vero cells.